Neuronal loss without amyloid‐β deposits in the thalamus and hippocampus in the late period after middle cerebral artery occlusion in cynomolgus monkeys. (21st July 2019) - Ouyang, Fubing; Chen, Xinran; Chen, Yonghong; Liang, Jiahui; Chen, Yicong; Lu, Tao; Huang, Weixian; Zeng, Jinsheng
Abstract: Conflicting evidence exists regarding whether focal cerebral infarction contributes to cerebral amyloid‐β (Aβ) deposition, as observed in Alzheimer's disease. In this study, we aimed to evaluate the presence of Aβ deposits in the ipsilateral thalamus and hippocampus 12 months post‐stroke in non‐human primates, whose brains are structurally and functionally similar to that of humans. Four young male cynomolgus monkeys were subjected to unilateral permanent middle cerebral artery occlusion (MCAO), and another four sham‐operated monkeys served as controls. All monkeys underwent magnetic resonance imaging examination on post‐operative day 7 to assess the location and size of the infarction. The numbers of neurons, astrocytes, microglia and the Aβ load in the non‐affected thalamus and hippocampus ipsilaterally remote from infarct foci were examined immunohistochemically at sacrifice 12 months after operation. Thioflavin S and Congo Red stainings were used to identify amyloid deposits. Multiple Aβ antibodies recognizing both the N‐terminal and C‐terminal epitopes of Aβ peptides were used to avoid antibody cross‐reactivity. Aβ levels in cerebrospinal fluid (CSF) and plasma were examined using enzyme‐linked immunosorbent assay. The initial infarct was restricted to the left temporal, parietal, insular cortex and the subcortical white matter, while the thalamus and hippocampus remained intact. Of note, there were fewer neurons and more glia in the ipsilateral thalamus and hippocampus in the MCAO group at 12 months post‐stroke compared to the control group (all P < 0.05). However, there was no sign of extracellular Aβ plaques in the thalamus or hippocampus. No statistically significant difference was found in CSF or plasma levels of Aβ40, Aβ42 or the Aβ40 /Aβ42 ratio between the two groups ( P > 0.05). These results suggest that significant secondary neuronal loss and reactive gliosis occur in the non‐affected thalamus and hippocampus without Aβ deposits in the late period after MCAO in non‐human primates.